2023
DOI: 10.35848/1347-4065/acc4ce
|View full text |Cite
|
Sign up to set email alerts
|

Detection of fish passing through a narrow path using reflected and transmitted ultrasonic waves

Abstract: The properties of echoes and transmitted waves from a fish body, in megahertz bands, were investigated to construct a fish detection method in a narrow path by a simple measurement structure using a pair of transducers. Experiments were performed in a water tank using dead Japanese jack mackerel (Trachurus japonicus). From the echoes, the outlines of fish could be observed. High amplitudes of echoes from the swim bladder and fins were observed, while relatively low amplitudes of echoes were observed from other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The increases in amplitude and the number of peaks in the echoes and the decreases in amplitude and ΔTOF in the backwall echoes and transmitted waves were observed in each of the nine and five passing events of fish samples 1 and 2, respectively. These results obtained from free-swimming goldfish appeared to show a similar pattern to those we obtained previously using dead Japanese jack mackerel, 31) despite the smaller size of goldfish compared with jack mackerel. This experiment has shown for the first time that backwall echoes can be affected by fish, as observed in the transmitted waves.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The increases in amplitude and the number of peaks in the echoes and the decreases in amplitude and ΔTOF in the backwall echoes and transmitted waves were observed in each of the nine and five passing events of fish samples 1 and 2, respectively. These results obtained from free-swimming goldfish appeared to show a similar pattern to those we obtained previously using dead Japanese jack mackerel, 31) despite the smaller size of goldfish compared with jack mackerel. This experiment has shown for the first time that backwall echoes can be affected by fish, as observed in the transmitted waves.…”
Section: Resultssupporting
confidence: 89%
“…[39][40][41][42][43] We observed decreased amplitude and time-of-flight (TOF) in waves transmitted through a fish's body. 31) Our earlier findings therefore showed that fish can be detected using MHz-band ultrasound, and the combined use of echoes and transmitted waves can increase the amount of information obtained about fish compared with the use of echoes only. However, in our previous study we used dead Japanese jack mackerel, Trachurus japonicus, for our experiments; the validity of this type of measurement for freeswimming fish has not yet been verified.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations